Antioxidant activity of herbal tea prepared from Cosmos caudatus leaves at different maturity stages - Fatanah, Dian Nashiela; Abdullah, Noriham; Hashim, Nooraain; Abdul Hamid, Azizah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Herbal tea is widely consumed around the world because people believed that it contained high amount of antioxidant. However, usage of different maturity of the plants as raw materials could affect the antioxidant capacities in herbal tea. Hence, this paper reports the antioxidant activity of herbal tea prepared from Cosmos caudatus at different maturity namely young, mature and old leaves. The analyses carried out were total phenolic content (TPC), total flavonoid content (TFC), ferric reducing antioxidant power (FRAP) and DPPH (2-2-diphenyl- 1-picrylhydrazyl) radical scavenging assays. Based on the results obtained, herbal tea prepared from young leaves had significantly strong (p<0.05) antioxidant activity for all assays tested than herbal tea prepared from mature and old leaves. In fact, TPC and TFC exhibited a strong positively correlation with reducing power but inversely correlated with DPPH scavenging activity indicating that these compounds are major contributors to the antioxidant activity. Thus, this shows that antioxidant activity in C. caudatus leaves reduced with increase maturity and hence it is recommended to use young leaves for herbal tea preparation since it possessed good antioxidant activity which benefits human health.